Exploring the current and future role of the pharmacists in osteoporosis screening and management in Malaysia - Toh, Li Shean; Lai, Pauline Siew Mei; Othman, Sajaratulnisah; Shah, Amir; Dang, C.P.L.; Low, Bee Yean; Wong, Kok Thong; Anderson, Claire (Springer Verlag, 2018)
Background Several studies have found that pharmacists can assist in screening and prevention of osteoporosis by referring patients for bone mineral density scans and counselling on lifestyle changes. In Malaysia, screening osteoporosis in all elderly women is not mandatory due to its cost. One approach to address this gap is to develop a pharmacist-led osteoporosis screening and prevention program. However, there is a paucity of data on the perspectives of Malaysian pharmacists in this area. Objective To explore the perspective of stakeholders (policy makers, doctors, pharmacists, nurses and patients) towards the role of pharmacists in osteoporosis screening and management. Setting A primary care clinic located within a teaching hospital in Kuala Lumpur, Malaysia. Method Patients (n = 20), nurses (n = 10), pharmacists (n = 11), doctors (n = 10) and policy makers (n = 5) were individually interviewed using a semi-structured topic guide. Purposive sampling was used. Interviews were transcribed verbatim and analysed using thematic analysis. Main outcome measure Perspective of stakeholders on the current and future role of pharmacists. Results All participants perceived pharmacists to be suppliers of medication, although there was some recognition of roles in providing medication advice. Nonetheless, these stakeholders were eager for pharmacists to expand their non-dispensing roles towards counselling, creating awareness and screening of osteoporosis. Interviewed pharmacists referred to their current role as ‘robotic dispensers’ and unanimously agreed to spread out to osteoporosis management role. Conclusion Under stakeholders there is a willingness to expand the role of pharmacists in Malaysia to non-dispensing roles, particularly in osteoporosis screening and management.